Opportunity pendidikan: Transformasi di era disrupsi dan revolusi industri 4.0 - Musyarofah, Umi Mufidatul; Nuzula, Ilmi Firdausi (Maliki Interdisciplinary Journal, 2024)
Disruption is an innovation, which can change the entire old order system by replacing it with the latest innovation. This innovation can replace old physical technology with digital technology that can replace something new, efficient and also useful. Meanwhile, in the industrial era 4.0, machines and factories will be connected, exchange data, work together, and be able to make decisions collectively. The industrial era 4.0 offers efficient use of time and resources, cost savings and increased income and helps add innovation to the industry. The old industry will of course be replaced by the newest industry because it is more efficient. Therefore, we must be able to anticipate well so that we can see new opportunities in the future. Skills in the field of industrial transformation knowledge education are expected to be truly well prepared, because in this sophisticated era, humans live side by side with smart machines in the workplace.